AUSTRAL: 10 YEARS OF SOUTH-SOUTH COOPERATION - Visentini, Paulo; Thudium, Guilherme (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Ever since the founding of NERINT, in 1999, our team of researchers planned the creation of a scientific journal that would disseminate their research, worldview, and establish a dialogue with academics from other nations and with members of the Brazilian diplomatic body. The periodical had to reflect the perspective of the developing world: the “South”. And this endeavour came to life exactly a decade ago, with the launch of AUSTRAL: Brazilian Journal of Strategy and International Relations.